Impact of Fog Levels on Free-Flow Speeds in Mixed Traffic Conditions - Angshuman Pandit; Anuj Kishor Budhkar (Communications)
The effect of fog levels on drivers' free-flow speeds for various vehicles in mixed traffic conditions is examined in this research. Visibility and free-flow speeds from eight highways are simultaneously collected and analyzed. The findings show distinct driver behavior patterns under different fog conditions. In dense fog, small visibility improvements lead to linear speed increases, while in light fog, speeds are mostly unchanged, though drivers maintain higher speeds than in clear conditions. Regardless of a vehicle type, driving patterns in fog are similar, though specific speeds differ. Cars tend to drive dangerously fast, while trucks remain slower due to limited manoeuvrability. This study offers insights for operational strategies in dense fog, supporting the use of dynamic warning systems and variable speed limits to reduce unsafe speed variations and potential crashes in low visibility.